Peran Badan Usaha Milik Desa dalam Meningkatkan Pendapatan Masyarakat Melalui Usaha Produksi Batako di Desa Matua - Janwar Surya Ardi; Samsudin Samsudin; Fahru Mauzu (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the role of the Village-Owned Enterprise (BUMDes) in increasing community income through a brick-making business unit in Matua Village, Woja Subdistrict, Dompu Regency. The method used is a descriptive qualitative approach. Primary data were collected through participatory observation and in-depth interviews with key informants selected via purposive sampling, including the Village Head, the BUMDes Director, unit managers, production workers, and consumer members of the community, while secondary data were obtained from BUMDes financial reports. Data analysis applied the Miles and Huberman interactive model (reduction, data presentation, and drawing conclusions) with validity testing using source and technique triangulation. The research results indicate that the Matua Village BUMDes plays a significant role as a central facilitator in breaking the cycle of seasonal unemployment for youth and farm laborers while simultaneously curbing the pace of urbanization. This brick-making business unit has been proven to increase workers’ monthly net income by 30% to 50% through a flexible system of daily wages and piecework. This increase in disposable income has a positive impact on the quality of life for workers’ families, particularly regarding nutritional needs and the continuity of children’s education, and creates a domino effect that accelerates the internal economic circulation of the village.